Factors Related to Health Informatics Competencies for Nurses—Results of a National Electronic Health Record Survey. Issue 8 (August 2019) - Kinnunen, Ulla-Mari; Heponiemi, Tarja; Rajalahti, Elina; Ahonen, Outi; Korhonen, Teija; Hyppönen, Hannele
Abstract : In 2015, the Finnish Ministry of Social Affairs and Health published an eHealth and eSocial strategy with key objectives that by 2020 health information systems will be smart and providers will be able to maximize their use. Measures include improving system usability and decision support, involving professionals in system and service development, and increasing professionals' training in information management, electronic documentation, data protection, and data security. The aim of this study was to explore the level of nurses' informatics competencies and sufficiency of in-house training regarding technology-induced changes in work practices. An electronic questionnaire produced by the National Institute of Health and Welfare was sent in February to April 2017 to 29 283 Finnish working-age nurses, community nurses, and midwives; 3607 replies were received. Respondents rated their overall informatics competency relatively high, with the lowest competency scores on terminology-based documentation (Finnish Care Classification) and patient-related digital work. Education, electronic health record system used, experience using electronic health record systems, sufficiency of training, higher levels of technical functionality, ease of use, and usefulness were all associated with competency and remained significant after all adjustments. One-third of the respondents felt that they had not received sufficient training. Age and participation in system development were associated with experiences of sufficiency of training.